HUBUNGAN MINAT DAN DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN MOTIVASI CALON SARJANA KEPERAWATAN UNTUK MELANJUTKAN PROFESI NERS DI UNIVERSITAS PAHLAWAN - MOLINA SARI MUTIA; GUSMAN VIRGO; SYAFRIANI SYAFRIANI (Jurnal Ners, 2020)
Professional program is a process of socializing students in gaining real experience to achieve professional skills (intellectual, interpersonal, non-technical) in carrying out nursing care to patients/ clients. The purpose of this study was to determine the interest relationship between and social support peer with the motivation of prospective nursing graduates to continue the nursing profession at Uptt. This type of research is quantitative with sectional design study. This research was conducted on 01 July-07 July 2020 with a total sample of 62 people obtained using a total sampling technique. The population in this study were all nursing students of 2016 class at Universitas Pahlawan Tuanku Tambusai Riau. The data collection technique used a questionnaire. The data analysis used was univariate and bivariate analysis with Fisher's Exact test. The results show that there is a relationship between interest and motivation p-value of 0.000 with a precise correlation of 0.704 and the relationship between peer social support and the motivation of the nursing graduate to continue the Nurse Profession at Universitas Pahlawan Tuanku Tambusai Riau p-value 0.002